(untitled) (Epidemiology, Biostatistics, and Public Health, 2025)
Alcohol poses a significant threat to public health in Ireland. In 2026, Ireland is due to introduce a mandatory alcohol warning label (AWL). Using a convenience sample of students and staff at an Irish Technological University (TU), this research sought to explore support for current and potentially expanded alcohol control measures. Online survey data was collected from 335 participants. Analysis revealed a very high level of support for the forthcoming introduction of Ireland’s AWL. Additionally, there was considerable support for a broader range of AWLs. More than half of the respondents supported the introduction of bland packaging on alcohol containers, and over 60% supported the introduction of more explicit tobacco-style graphic warnings on alcohol. Over 40% of respondents reported that AWLs would impact their intention to consume alcohol.